Clinical Features and Treatment Response in Immune-Mediated Small Fiber Neuropathy with Trisulfated Heparin Disaccharide or Fibroblast Growth Factor Receptor 3 Antibodies. Issue 4 (June 2021) - Zeidman, Lawrence A.; Kubicki, Konrad
Abstract: Objective: Novel antibodies to trisulfated heparin disaccharide (TS-HDS) and fibroblast growth factor receptor 3 (FGFR-3) have been recently described in otherwise cryptogenic small fiber neuropathy (SFN) cases. Our goal was to further describe clinical features in such cases and to analyze treatment responses. Methods: In a retrospective analysis, 40 cases of cryptogenic SFN in a university neuropathy clinic were identified. Of these, TS-HDS and FGFR-3 cases were identified, and clinical features and treatment responses were analyzed. Results: In this cohort, 95% were women, and 55% had either TS-HDS or FGFR-3 antibodies (77% of these had TS-HDS). Of the seropositive group, 41% had a nonlength dependent epidermal nerve fiber density on skin punch biopsy (OR = 1.80). In the seropositive group, 82% had neuropathic pain as their primary symptom (OR = 1.73). Also 32% of seropositive patients reported widespread pain (OR = 1.63). 63% of seropositive cases presented acutely (OR = 11.0). In the seropositive group, 23% had an initial erroneous diagnosis (OR = 1.47). Eight seropositive patients improved on intravenous immunoglobulin treatment, with a 42% reduction in pain scores ( P = 0.02), a 44% reduction in the Utah Neuropathy Score, and improved epidermal nerve fiber density post-treatment. Conclusions: TS-HDS and FGFR-3 antibodies may be present in a high proportion of cryptogenic SFN cases with acute onset, nonlength dependent pathology, and primary neuropathic and widespread pain. They are often misdiagnosed as other conditions including fibromyalgia. These cases may be responsive to immune treatment, especially with intravenous immunoglobulin.